Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s12603-016-0806-y
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of a Mediterranean type diet on inflammatory and cartilage degradation biomarkers in patients with osteoarthritis

Abstract: ObjectivesTo investigate the effects of a Mediterranean type diet on patients with osteoarthritis (OA).ParticipantsNinety-nine volunteers with OA (aged 31 - 90 years) completed the study (83% female).SettingSoutheast of England, UK.DesignParticipants were randomly allocated to the dietary intervention (DIET, n = 50) or control (CON, n = 49). The DIET group were asked to follow a Mediterranean type diet for 16 weeks whereas the CON group were asked to follow their normal diet.MeasurementsAll participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 15 publications
1
87
0
1
Order By: Relevance
“…The modulation of inflammatory processes may be an important factor in patients with SLE that could explain the deleterious effect of the consumption of high levels of free sugar. It is thought that the resulting reduction in disease activity may be secondary to the mechanisms that decrease inflammation and activate autoimmunity pathways [34,35]. Furthermore, it has been reported that dietary sugar may promote de novo synthesis of free fatty acids (FFA) in the liver [36,37], which may produce FFA metabolites, thus triggering inflammatory processes and the formation of reactive oxygen species [38].…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of inflammatory processes may be an important factor in patients with SLE that could explain the deleterious effect of the consumption of high levels of free sugar. It is thought that the resulting reduction in disease activity may be secondary to the mechanisms that decrease inflammation and activate autoimmunity pathways [34,35]. Furthermore, it has been reported that dietary sugar may promote de novo synthesis of free fatty acids (FFA) in the liver [36,37], which may produce FFA metabolites, thus triggering inflammatory processes and the formation of reactive oxygen species [38].…”
Section: Discussionmentioning
confidence: 99%
“…A nutrition study highlighted that on 99, mainly female volunteers aged 31-90 a 16 weeks Mediterranean type diet decreases serum IL-1β with 47%, and serum COMP with 8%. 73 Shan et al measured higher serum levels of proinflammatory cytokines IL-21, IL-17A and IFN-γ at 40 individuals recently diagnosed with OA. 74 In animal models, synovial levels of pro-inflammatory cytokines can be used to monitor moderate physical activity.…”
Section: Proinflammatory Cytokines and Chemokinesmentioning
confidence: 99%
“…The consistent MD consumption was associated with less pain and lower disability, suggesting that MD has a beneficial effect on various aspects associated with disability leading to healthier aging 20 . A Clinical trial investigated the effect of MD in cartilage degradation and inflammatory biomarkers, in osteoarthritis patients, pointed out that participants with the MD intervention, had improvements in their dietary habits and this led to weight loss 21 . Research has shown that weight loss is associated with improvements in pain and mobility in patients with OA 21,22 .…”
Section: The Role Of Mediterranean Diet Against Osteoarthritismentioning
confidence: 99%
“…A Clinical trial investigated the effect of MD in cartilage degradation and inflammatory biomarkers, in osteoarthritis patients, pointed out that participants with the MD intervention, had improvements in their dietary habits and this led to weight loss 21 . Research has shown that weight loss is associated with improvements in pain and mobility in patients with OA 21,22 . Besides, there was a reduction of IL-1a and cartilage oligomeric matrix protein in serum "sCOMP" (cartilage degradation significant marker) in the MD intervention group.…”
Section: The Role Of Mediterranean Diet Against Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation